Modeling and usage of a sustainametric technique for measuring the life-cycle performance of a waste management system: A case study of South Africa - Aboginije, Ademilade; Aigbavboa, Clinton; Thwala, Wellington (Frontiers in Sustainability, 2023)
When designing a waste system via circular economy initiatives, the necessary guiding principles that should be observed includes; sustainability, eco-efficiency of material, precautionary principles, cooperation and participation, polluter-pays-principles, producer responsibility, life-cycle system thinking, and principles of true cost, efficiency, and minimal costs. However, there is a prerequisite for measuring the waste management used in any construction project. Therefore, to measure the sustainability performance of a waste management system, this study introduces statistical techniques to conduct a performance rating of a waste management system. The focus is to show how sustainable waste management strategies are employed in developing countries, especially in the South African construction project. In this study, a sustainametric technique is viable to measure the life-cycle sustainability performance of a waste management system in South Africa. Findings show that the model adopted for the score and the result of each metric used for the measurement are viable. From every indication, the South African construction industry is hitherto to fully adopt and implement a sustainable waste management system for effective waste minimization, although the overall performance shows that the waste sectors are thriving and improving in their approach to waste management. In conclusion, the is an urgent need to upscale and upgrade the current waste management system applied to minimizing waste in the South Africa construction project.